The Quality of Literature on Jurisprudence as the Most Important Prerequisite for the Formation of a Modern Lawyer - Vladimir Valentinovich Kozhevnikov (Britain International for Academic Research (BIAR-Publisher), 2025)
Believing that high-quality literature on jurisprudence is the most important prerequisite for the training of practicing lawyers, the author, based on an analysis of one of the textbooks, shows that the former often does not meet the relevant requirements. In conclusion, it is emphasized that the problem under consideration remains relevant at the present time and its solution necessarily requires positive moral responsibility of both authors of educational literature and responsible editors and reviewers.